Deciphering the role of chemisorbed CO in CO2 methanation: kinetic and mechanistic investigation over monometallic (Ru) and bimetallic (Ru-Ni) catalysts - Dongapure, Pavan; Tekawadia, Jyoti; Naidu, V. Satyam; Devi, R. Nandini (Catalysis Science & Technology, 2024)
Supported metal catalysts have made prominent contributions to CO2 mitigation through conversion into useful chemicals. However, intermediates and mechanisms involved in this process remain ambiguous. Herein, we present the kinetics, mechanistic route and impact of chemisorbed CO in CO2 methanation on Ru/gamma-Al2O3 and Ru-Ni/gamma-Al2O3 catalysts. Both the catalysts show minimal variation in adsorbed species on changing the duration of reduction, as confirmed through in situ IR spectroscopy. A notable observation is that the adsorbed CO exhibits a red shift at a longer reduction time and a more reactive nature on the Ru/gamma-Al2O3 surface. Conversely, stable bridged CO mode is detected on Ru-Ni/gamma-Al2O3 under similar conditions, leading to catalyst poisoning in all instances. This indicates that pre-reduction duration does not have much effect on the surface but interference of CO has more effect at lower concentrations of reactant gases. In situ XRD analysis reveals limited changes in the metallic or mixed oxide species during these conditions. Reaction kinetic analysis showed that Ru-Ni/gamma-Al2O3 has better rate performance at higher concentrations of CO2, whereas Ru/gamma-Al2O3 exhibits better rate performance at lower concentrations. The activation energy was found to be 74.07 kJ per mole for Ru/gamma-Al2O3 and 89.38 kJ per mole for Ru-Ni/gamma-Al2O3. The turnover frequency (TOF) is directly proportional to the rate of formation of methane.